Index Based Irrigation Suitability of Ramsar Sites (Rara and Ghodaghodi) in Western Nepal - Bhatta, Rita; Gurung, Smriti; Joshi, Rajendra; Tuladhar, Shrija; Regmi, Dikshya; Tripathee, Lekhendra; Paudyal, Rukumesh; Guo, Junming; Kang, Shichang; Sharma, Chhatra Mani (Journal of Nepal Chemical Society, 2024)
The present study highlights the water quality of two important Ramsar sites of western Nepal (Ghodaghodi and Rara lakes) in terms of irrigation use. Based on land use patterns and location accessibility, 13 sites in Ghodaghodi and 18 in Rara were considered and the samplings were performed in the pre-monsoon and post-monsoon seasons. Different physicochemical parameters such as pH, electrical conductivity (EC), total dissolved solids (TDS), total hardness (TH), major cations, and anion (Na+, K+, Ca2+, Mg2+, and HCO3-) were measured. The calculated indices were permeability index percentage (PI), sodium percentage (%Na), sodium adsorption ratio (SAR), magnesium hazard ratio (MAR), residual sodium carbonate (RSC), and Kelly’s index (KI). Major ions were analyzed using ion chromatography including field and procedural blanks to maintain quality standards, whereas on-site parameters were measured by using standard multi-meter probes. The studied irrigation water quality parameters (pH, EC, TDS, TH) and indices (PI, MAR, RSC, KI, SAR, and %Na) fall within the permissible limit in both lakes, indicating the suitability of such water for irrigation purposes. In addition, based on the SAR vs. EC plot, all the results from both lakes fall in the S1 category, signifying low sodium hazard. Concerning EC, most of the samples demonstrate the C1 category and few are in the C2 category (in Ghodaghodi) whereas the C1 category predominates for Rara. According to IWQI, all water samples in both lakes fall in the class I category, which supports the results of other indices indicating the suitability of water for irrigation purposes.